Mechanical Properties of Steel Fiber-Reinforced Concrete Tunnel Secondary Lining Structure and Optimization of Support Parameters - Zijian Wang; Yunchuan Wang; Xiaorong Wang; Baosheng Rong; Bin Zhang; Liming Wu; Chaolin Jia; Zihang Huang (Buildings)
To enhance the economic and safety aspects of tunnel structural design, this study optimizes the mix proportion of steel fiber-reinforced concrete (SFRC). It investigates the stress characteristics and support parameters of SFRC secondary lining structures via small-scale model tests and finite element analysis. The research focuses on the cracking process, deformation, and stress characteristics of SFRC linings under various loads. Compared with conventional reinforced concrete tunnels, SFRC tunnels show a significant increase in lining stiffness and load capacity, with a 20% reduction in reinforcement yielding load. When the damage factor is 0.43, the addition of steel fibers increases compressive stress by 22.18%. Using ABAQUS, simulations of SFRC linings with thicknesses ranging from 400 mm to 600 mm and reinforcement ratios of 0% to 0.28% were conducted. The results indicate that a 450 mm thick SFRC lining matches the mechanical performance of a 600 mm thick conventional reinforced concrete lining. Notably, an SFRC lining with a 0.20% circumferential reinforcement ratio equals a conventional lining with a 0.28% reinforcement ratio in overall mechanical performance.